Beyond the grave - Watson, Jude (39 clues, 2009)
Amy and Dan, following a clue found in Book 3, set out to uncover details about the origins of the rivalry between the Tomas and Ekaterina branches of their family, not realizing they are headed right into the hands of the enemy.